The group-reference effect and soldiers' recognition memory. Issue 2 (7th February 2021) - Li, Qiong; Liang, Ting; Zhou, Eqiao; Pan, Xinxing; Zhang, Xiaobin
ABSTRACT: Previous research has consistently found that the self-reference effect (SRE) is equal to, or stronger than, the group-reference effect (GRE) for memory performance. The military strongly emphasises group identity; this study investigated whether the GRE was stronger than the SRE for soldiers. Soldiers were recruited to participate in Experiments 1 and Experiment 2. Experiment 1 revealed that recognition was better under the group-reference condition than the self-reference condition. Experiment 2 was identical to Experiment 1, with the exception that the recognition test required participants to use "remember" / "know" / "guess" judgments. The results were consistent with those of Experiment 1, that is, the GRE contributed to better recognition than the SRE, but the difference was statistically significant only for "know" responses. Using a less cohesive group (university students) as participants, Experiment 3 found that the GRE was not superior to the SRE for memory recognition, which indicated that the results of Experiments 1 and 2 were exclusive to soldiers. The ﬁndings suggest that soldiers' sense of self might be unique, and that an ingroup sense of self might be dominant for soldiers.